Innovative Leadership, Organizational Agility, Adaptability, and Organizational Commitment Influencing the Organizational Excellence of Aesthetic Clinics in Bangkok - Tongsiripaisri, Russamee; Siraphatthada, Yananda; Teppratuangtip, Peerawee; Thitivesa, Duangkamol (Ph.D. in Social Sciences Journal, 2026)
This research article aims to (1) examine the level of innovative leadership, organizational agility, adaptability capability, organizational commitment, and organizational excellence of aesthetic clinics in Bangkok; (2) investigate the influence of innovative leadership, organizational agility, adaptability capability, and organizational commitment on the organizational excellence of aesthetic clinics in Bangkok; and (3) develop a model of organizational excellence for aesthetic clinics in Bangkok. A mixed-method research approach was employed. In the quantitative phase, the sample consisted of 320 executives or owners of aesthetic clinic businesses in Bangkok. The sample size was determined based on the ratio of observed variables at 1:20. Data were collected using questionnaires and analyzed using structural equation modeling (SEM). In the qualitative phase, in-depth interviews were conducted with 20 key informants selected through purposive sampling, and the data were analyzed using content analysis. Finding are as follows: (1) innovative leadership, organizational agility, adaptability capability, organizational commitment, and organizational excellence were found to be at the highest level; (2) Innovative leadership, organizational agility, adaptability, and organizational commitment have both direct and indirect positive effects on organizational excellence in aesthetic clinics in Bangkok, with statistical significance at the .05 level; and (3) the development of an organizational excellence model for aesthetic clinics in Bangkok, named the IOACE Model, serves as a strategic driving mechanism that leads to systematic and sustainable organizational excellence.